Oxidative Depolymerization of Lignin Using a Novel Polyoxometalate-Protic Ionic Liquid System - De,Gregorio GF; Prado,R; Vriamont,C; Erdocia,X; Labidi,J; Hallett,JP; Welton,T (ACS Sustainable Chemistry and Engineering, 2016)
Oxidative depolymerization of lignin obtained from pine and willow can be achieved in a novel system encompassing the ionic liquid (IL) 1-butylimidazolium hydrogensulfate coupled with a vanadium based polyoxometalate (POM) under oxygen rich conditions. Along with an array of phenols and functionalized aromatics, vanillin and syringaldehyde were the main products extracted from the IL. The overall yield of aldehyde products were shown to be higher on lignin samples obtained with shorter pretreatment times, with vanillin being the exclusive aldehyde product obtained from pine. In the presence of molecular oxygen, the highest yield of aldehyde products was obtained when 5 wt % of the POM relative to the IL was employed and constituted the major product in the extracted oils. This system succeeds in exploiting the ability of ILs to depolymerize lignin and the remarkable properties of the POM to oxidize the lignin fragments into useful platform chemicals.